PENERAPAN TEKNIK MENU ENGINEERING DALAM MENINGKATKAN PENJUALAN DAN KEUNTUNGAN PADA HOTEL SWISSBELL HARBOURBAY BATAM - Ferdinand, Reagan; Saputra, Eryd (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2024)
The objective of this research is to investigate the application of Menu Engineering techniques in improving sales and profits at Swiss-Bell Harbourbay Batam Hotel. The research employs a qualitative methodology, utilizing data collection techniques such as interviews, observations, and strategic analysis using menu engineering. The menu analysis, conducted through menu engineering, revealed a total of 61 food items at Swiss-Café Swiss-Bell Harbourbay Batam, categorized into stars, puzzles, plowhorses, and dogs. Among these, 15 food items fall under the stars classification, constituting 25 of the total menu items. The stars category represents a blend of high menu variety and the highest contribution margin, featuring food items from the Swiss Café. Furthermore, the dogs classification comprises 28 menu items, constituting 46 of the total, indicating the highest quantity among all categories.